PENGARUH BRAND IMAGE, PROMOSI MEDIA SOSIAL, DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI XES SHOES INDONESIA - Suyanti, Royandi; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2023)
Purchasing decisions are used as an important component when keeping consumers fromswitching. Purchasing decisions are consumer responses to differences in the level ofneeds and real results that are enjoyed after consuming a product/service. Purchasingdecisions have several factors that can influence them, including brand image, socialmedia promotions, and digital marketing. This study aims to analyze the effect of brandimage, social media promotion, and digital marketing simultaneously on purchasingdecisions at XES Shoes Indonesia. The design of this study uses research design andquantitative research methods. The data collection technique was by distributingquestionnaires to 222 respondents, namely consumers who made purchases at XESShoes Indonesia for the July-December 2022 period. The results of this study indicate thatbrand image, social media promotion, and digital marketing partially and simultaneouslyhave a significant effect on purchasing decisions. The results of the test for the coefficientof determination show that brand image, social media promotion, and digital marketingpartially and simultaneously have a significant effect on purchasing decisions by 43.2percent, while the rest are influenced by other variables not examined in this study.